Seminal plasma concentrations of Anti‐Müllerian hormone and inhibin B predict motile sperm recovery from cryopreserved semen in asthenozoospermic men: a prospective cohort study. (1st October 2014) - Nery, S. F.; Vieira, M. A. F.; Dela Cruz, C.; Lobach, V. N. M.; Del Puerto, H. L.; Torres, P. B.; Rocha, A. L. L.; Reis, A. B.; Reis, F. M.
Summary The rate of motile sperm recovery after cryopreservation is very variable and difficult to predict. Anti‐Müllerian hormone (AMH) and inhibin B are produced by Sertoli cells and released into the seminal plasma, where they could be functional markers of spermatogenesis and sperm resistance to thermal stress. The aim of this study was to evaluate whether seminal plasma levels of AMH and inhibin B predict sperm recovery after cryopreservation. The study included 153 men enrolled prospectively during a semen analysis. The cohort was stratified by the fresh semen characteristics into: normal (n = 52), high sperm count (n = 55), asthenozoospermia (n = 23), and oligozoospermia (n = 23). The main outcome measure was motile sperm recovery rate, defined as post‐thaw total motile sperm count × 100/pre‐freezing total motile sperm count. In men with asthenozoospermia there was a significant correlation between motile sperm recovery rate and the pre‐freezing concentrations of AMH (r = 0.522, p < 0.05) and inhibin B (0.471, p < 0.05). In this group, the areas under the receiver operating characteristic curves of AMH and inhibin B for prediction of ≥50% motile sperm recovery after cryopreservation were, respectively, 0.808 and 0.638. AMH was particularly useful, with sensitivity of 0.85, specificity of 0.80, positive predictive value of 0.84 and negative predictive value of 0.80. The sensitivity, specificity, positive, and negative predictive values of inhibin B for the same outcome were, respectively, 0.62, 0.60, 0.67, and 0.55. The median motile sperm recovery rate was 83% when seminal plasma AMH concentration was ≥0.84 ng/mL, vs. 27% when AMH concentration was <0.84 ng/mL (p < 0.05). In other patient groups, there was no correlation between the two hormone levels in seminal plasma and the motile sperm recovery rate. In conclusion, seminal plasma AMH and inhibin B concentrations correlate with and can be used to predict motile sperm recovery after semen cryopreservation in asthenozoospermic men.